(untitled) (Research, Society and Development, 2024)
Atherosclerosis is a dysfunction that affects the endothelium lining the artery, making it more susceptible to the deposition of LDL in the intima, its innermost layer. Oxidized LDL stimulates endothelial cells to secrete molecules that promote the migration of monocytes from the bloodstream to the injured region. In the tissue, monocytes differentiate into macrophages that phagocytosis the oxidized LDL particles and form foam cells that trigger the atheroma plaque that causes the stiffening of the vessels and hinders the passage of blood, and its rupture generates cardiovascular complications such as heart attack and stroke. Dietary habits play a determining role in this pathology, where foods that are sources of saturated and trans fats can favor the development of atherosclerosis by increasing serum LDL concentrations. In contrast, a diet with foods that are sources of more and less soluble fiber, unsaturated fatty acids, bioactive compounds, and antioxidant micronutrients prevents the development of atherosclerosis, as it contributes to the reduction of serum LDL levels and the neutralization of reactive species derived from oxygen and nitrogen. The aim of this study was to conduct a narrative review of the biochemical and immunological aspects of atherosclerosis, and the dietary factors that contribute to its prevention and/or treatment. Since this is a disease that causes serious complications to the cardiovascular system, such as heart attack and stroke, it is important to apply prophylactic measures to prevent such comorbidity.